Journalism today - Ferguson, Donald L.; Patten, Jim.; Wilson, Bradley (Lincolnwood, Ill. : National Textbook, 1998)
Discusses the history and responsibilities of the Media, the gatheri ng, writing, and presentation of news, and the future of journalism as technology changes.
Includes index.
Keywords: Journalism; Journalism, High School